An Analysis on Adult Learners’ Satisfaction in Online Education Programmes - Ng, Hueyzher; Baharom, Sakina Sofia (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The demand for online programmes is continuously increasing at varying degrees, with the major appeal coming from adult learners whom are managing with the numerous demands from other work and life domains. These adult learners have their own varied expectations from the online learning process. The purpose of this paper is to investigate the degree to which other predictors contribute to adult learners’ satisfaction in online learning environment. A mixed-methods design was used, selecting both quantitative methods (utilizing survey research) and qualitative methods (employing open-ended questionnaire items), gathering the feedback of 200 adult learners whom comprises of secondary school teachers and college level teachers, enrolled in professional online courses. The online courses were designed using a problem-centered and case-based approach to learning and utilized technologies including learning management system (LMS) such as Moodle as well as functions from the LMS. The results showed that the items such as learner-content interaction, self-regulated learning design, and Internet self-efficacy were good predictors of students’ satisfaction. Implications of these findings for higher education in providing blended or online programmes for adult learners are also discussed.